PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI, DIMEDIASI MOTIVASI KERJA - Solikhin, Solikhin; Purwani, Tri; Erbito, Yoseph; Marwati , Sri (Mount Hope Management International Journal, 2025)
This research aims to determine the influence of the transformational leadership and physical work environment on employee performance with work motivation as a Mediating Variable at Dinas Koperasi Usaha Kecil Dan Menengah, Perindustrian Dan Perdagangan yang ada di Kab. Bantul This research design is quantitative research with a population of 122 employees anda sample of 122 respondents. The data collection method in this research uses the questionnaire method. Data analysis used in this research uses a Structural Equation Model(SEM) approach based on Partial Least Square (PLS). The results of this research show that the Transformational leadership has a positive influence on performance, transformational leadership has a positive influence on work motivation, the physical work environment does not affect performance, the physical work environment has a positive influence on work motivation, work motivation has a positive influence on performance, there is a positive relationship between transformational leadership and performance mediated by work motivation, there is a positive relationship between the physical work environment and performance, mediated by work motivation.